Marginal and Internal Fit of Cobalt-Chromium Fixed Dental Prostheses Generated from Digital and Conventional Impressions. (3rd March 2014) - Svanborg, Per; Skjerven, Henrik; Carlsson, Pablo; Eliasson, Alf; Karlsson, Stig; Örtorp, Anders
Abstract : Objectives . Digital impressions are increasingly used and have the potential to avoid the problem of inaccurate impressions. Only a few studies to verify the accuracy of digital impressions have been performed. The purpose of this study was to compare the marginal and internal fit of 3-unit tooth supported fixed dental prostheses (FDPs) fabricated from digital and conventional impressions. Methods . Ten FDPs were produced from digital impressions using the iTero system and 10 FDPs were produced using vinyl polysiloxane (VPS) impression material. A triple-scan protocol and CAD software were used for measuring and calculating discrepancies of the FDPs at 3 standard areas: mean internal discrepancy, absolute marginal gap, and cervical area discrepancy. The Mann-Whitney U test was used for analyzing the results. Results . For conventional and digital impressions, respectively, FDPs had an absolute marginal gap of 147 μ m and 142 μ m, cervical area discrepancy of 69 μ m and 44 μ m, and mean internal discrepancy of 117 μ m and 93 μ m. The differences were statistically significant in the cervical and internal areas (P < 0.001 ). Significance . The results indicated that the digital impression technique is more exact and can generate 3-unit FDPs with a significantly closer fit compared to the VPS technique.